Softgels

JP7651462B2Active Publication Date: 2025-03-26SUNSHO PHARMA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021551208
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-11
Filing Date
2020-09-25
Publication Date
2025-03-26
Estimated Expiration
2040-09-25

AI Technical Summary

Benefits of technology

【0009】 本発明では、ジェランガムを含有する新規なカプセル(ソフトカプセル)を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651462000001
    Figure 0007651462000001
  • Figure 0007651462000002
    Figure 0007651462000002
  • Figure 0007651462000003
    Figure 0007651462000003
Patent Text Reader

Abstract

Provided is a novel soft capsule. This soft capsule has a coating containing gellan gum and satisfies the following (A) and / or (B). (A) The disintegration time of the soft capsule measured in water as a test liquid according to the disintegration test of the Japanese Pharmacopoeia is within 60 minutes. (B) The ratio (breaking strength / outer diameter) of the breaking strength (g) to the outer diameter (mm) is 210 or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a capsule (soft capsule), and more particularly to a capsule used in the fields of medicine, food, industry, etc. [Background technology]

[0002] Conventionally, various materials such as gelatin have been known as a shell base for soft capsules, and attempts to use gellan gum as such a material have also been made.

[0003] For example, Patent Document 1 describes a seamless disintegrable capsule containing a core and a shell, the shell comprising a gelling agent comprising gellan gum alone or in a mixture with other gelling agents, a filler, and a divalent sequestering agent. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5529415 Summary of the Invention [Problem to be solved by the invention]

[0005] As mentioned above, attempts to use gellan gum are being made, but many of them still seem to be insufficient. According to the inventors' investigations, gellan gum appears to be, among coating materials, a material that is difficult to adjust in terms of quality and physical properties (e.g., disintegrability in water, disintegrability in the mouth, etc.) as well as manufacturing and production, and it was found that much improvement is needed before it can be used as a capsule material. In particular, capsules using gellan gum as a coating material (e.g., capsules that do not substantially use gelatin or that use only small amounts of gelatin) may require a complicated process such as immersion in an aqueous solution containing a hardener that contains a divalent ion (such as calcium ion), as in Patent Document 1, or the water-disintegration properties of the resulting capsules may be poor, making it extremely difficult to find a form of capsule that can be produced and used effectively.

[0006] An object of the present invention is to provide a novel capsule or the like containing gellan gum. [Means for solving the problem]

[0007] As a result of intensive research into achieving the above-mentioned object, the inventors have found that novel capsules can be obtained by compounding monovalent metal ions with capsules containing gellan gum, and that such capsules have excellent physical properties (e.g., excellent water-disintegrability and relatively high strength, and even capable of achieving both of these properties, despite containing gellan gum), and further research led to the completion of the present invention.

[0008] That is, the present invention relates to the following inventions. [1] A capsule (soft capsule) having a shell containing gellan gum, which satisfies the following (A) and / or (B): (A) The disintegration time is within 60 minutes according to the Japanese Pharmacopoeia Disintegration Test Method using water as the test liquid. (B) The ratio of breaking strength (g) to outer diameter (mm) (breaking strength / outer diameter) is 210 or more. In addition, in this capsule, the shell may not contain (or may substantially not contain) gelatin. [2] A capsule (soft capsule) having a coating containing gellan gum and a monovalent metal ion. In addition, in this capsule, the shell may not contain (or may substantially not contain) gelatin. [3] The capsule according to [1] or [2], wherein (A) the disintegration time is within 60 minutes according to the Japanese Pharmacopoeia Disintegration Test Method using water as the test liquid, and (B) the ratio of breaking strength (g) to outer diameter (mm) (breaking strength / outer diameter) is 210 or more. [4] (C) A capsule according to any one of [1] to [3], in which the ratio of breaking distance (mm) to outer diameter (mm) (breaking distance / outer diameter) is 0.1 or more. [5] The capsule according to any one of [1] to [4], wherein the proportion of gellan gum in the shell is 5% by mass or more. [6] The capsule according to any one of [1] to [5], which contains a monovalent metal ion as a monovalent metal compound. [7] The capsule according to any one of [1] to [6], which contains a monovalent metal ion as at least one monovalent metal compound selected from an alkali metal halide, an alkali metal salt of an organic acid, and an alkali metal salt of a sugar or a polysaccharide. [8] The capsule according to any one of [1] to [6], which contains a monovalent metal ion at least as an alkali metal alginate. [9] The capsule according to any one of [1] to [8], wherein the proportion of monovalent metal ions, calculated as metal atoms, is 0.1 parts by mass or more per 100 parts by mass of gellan gum.

[10] The capsule according to any one of [1] to [9], wherein the shell contains another shell base in a ratio of 100 parts by mass or less per 100 parts by mass of gellan gum.

[11] A capsule according to any one of [1] to

[10] , wherein the shell contains a plasticizer.

[12] The capsule according to any one of [1] to

[11] , wherein the shell contains at least one plasticizer selected from polyhydric alcohols, sugar alcohols, disaccharides, polysaccharides, and derivatives thereof.

[13] The capsule according to any one of [1] to

[12] , wherein the outer diameter of the capsule is 0.1 to 15 mm.

[14] A capsule according to any one of [1] to

[13] , wherein the capsule has a coating rate of 3% by mass or more.

[15] A capsule according to any one of [1] to

[14] , which has a content and has a coating ratio of 3 to 50 mass %.

[16] The capsule according to any one of [1] to

[15] , wherein the standard deviation (SD) value of the breaking strength is 500 g or less, and the standard deviation (SD) value of the breaking distance is 1 mm or less.

[17] The capsule according to any one of [1] to

[16] , which is a seamless capsule.

[18] A method for producing a capsule according to any one of [1] to

[17] , comprising at least a capsule production step of obtaining capsules having a moisture content of 80% by mass or more and a ratio of breaking strength (g) to outer diameter (mm) (breaking strength / outer diameter) of 5.0 or more by a dropping method, and a drying step of drying the capsules obtained by this capsule production step. Effect of the Invention

[0009] The present invention provides a novel capsule (soft capsule) containing gellan gum.

[0010] In another embodiment of the present invention, a capsule (soft capsule) that contains gellan gum and has excellent solubility or disintegrability in water can be provided. In particular, such a capsule may be disintegrated in a relatively short time (e.g., within 60 minutes, particularly within 20 minutes) in the disintegration test of the Japanese Pharmacopoeia (17th revision).

[0011] The capsule (soft capsule) according to another embodiment of the present invention can have a relatively high strength. For example, such a soft capsule can have a relatively high shell strength even when it contains a content.

[0012] In another embodiment of the present invention, the capsule can have both excellent strength and water-disintegrability. According to the study by the present inventors, in a capsule containing gellan gum, there is usually a trade-off between strength and water-disintegrability, but in the present invention, by appropriately selecting the composition and ratio of the capsule, it is surprisingly possible to efficiently obtain a capsule that can have both strength and water-disintegrability.

[0013] Capsules according to another embodiment of the present invention can be efficiently manufactured even if they contain gellan gum. For example, such capsules can be manufactured without a soaking step as in Patent Document 1. Furthermore, cracking during capsule manufacturing and drying can be efficiently suppressed. Therefore, such capsules are also excellent in terms of mass productivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The capsule (soft capsule) of the present invention contains at least gellan gum. Such a capsule may contain, in particular, gellan gum and a monovalent metal ion. Such a capsule usually has gellan gum (and other components such as monovalent metal ions) in the membrane (capsule membrane). Specific soft capsules of the present invention include capsules consisting of a single sphere (membrane only) containing gellan gum (and other components such as monovalent metal ions), and capsules containing gellan gum (and other components such as monovalent metal ions) in the membrane (capsules containing contents and a membrane containing gellan gum and a monovalent metal ion).

[0015] Gellan gum is a linear heteropolysaccharide produced by the non-pathogenic microorganism Pseudomonas elodea. Gellan gum includes deacylated gellan gum, native gellan gum, etc., and can be used in the present invention without any particular limitation, but from the viewpoint of manufacturability of soft capsules, deacylated gellan gum may be preferably used.

[0016] Deacylated gellan gum is native gellan gum in which the acyl groups (e.g., acetyl groups and glyceryl groups) have been deacylated. It may be that all of the acyl groups have been deacylated (completely deacylated gellan gum) or that some (or partial) of the acyl groups have been deacylated (partially deacylated gellan gum).

[0017] In the partially deacylated gellan gum, the amount of acyl groups is not particularly limited, but for example, the degree of acylation expressed as the ratio of the peak intensity of the acyl groups to the peak intensity of the methyl groups in NMR measurement (analysis) may be 1.06 or less (e.g., less than 1.06, 1.05 or less, 1 or less, 0.95 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, 0.1 or less). The lower limit of the degree of acylation may be more than 0, and may be, for example, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, etc.

[0018] The proportion of gellan gum [or the proportion of gellan gum in the shell (if the capsule contains a content, the proportion of gellan gum in the shell)] is not particularly limited, but is 5% by mass or more (e.g., 10% by mass or more, 15% by mass or more, 18% by mass or more) in terms of solid content [or the proportion to the total components other than the solvent such as water (components constituting the shell)] from the viewpoint of improving capsule strength, etc., and may be 23% by mass or more, 25% by mass or more, 27% by mass or more, 30% by mass or more, 33% by mass or more. In addition, the upper limit is not particularly limited, and may be, for example, 80% by mass or less, 70% by mass or less, etc. from the viewpoint of operability during production, drying property of the capsule, etc.

[0019] The capsule (shell) may contain a monovalent metal ion. By including such a monovalent metal ion in the capsule (shell), it is easy to efficiently obtain a soft capsule having excellent physical properties (for example, strength and water disintegration). Monovalent metal ions (or monovalent metals) include alkali metal (eg, lithium, sodium, potassium, rubidium, cesium, francium) ions. The monovalent metal ions may be used alone or in combination of two or more kinds.

[0020] The capsule may contain a monovalent metal ion as the monovalent ion-containing compound. Examples of such compounds include inorganic compounds [e.g., alkali metal halides (e.g., lithium chloride, sodium chloride, potassium chloride)], organic compounds {e.g., alkali metal salts of organic acids (e.g., sodium acetate, sodium tartrate, sodium citrate), alkali metal salts of sugars or polysaccharides [e.g., alkali metal alginates (e.g., sodium alginate, potassium alginate)], etc.}. These may be used alone or in combination of two or more.

[0021] Organic compounds (for example, alkali metal salts of polysaccharides such as alkali metal alginates) are more preferable than inorganic compounds from the viewpoint of capsule formability, and among them, sodium alginate and potassium alginate, particularly sodium alginate, are more preferable.

[0022] In addition, gellan gum may contain alkali metals (for example, as alkali metal salts of the carboxyl groups that constitute gellan gum), but such alkali metals are not considered to be "monovalent metal ions" (monovalent metals) in this invention. In other words, in the present invention (capsule, coating), unless otherwise specified, "monovalent metal ion" means one that is added or blended separately from gellan gum [a monovalent metal (ion) that is not an alkali metal that gellan gum originally contains].

[0023] When a monovalent metal ion is contained, the proportion of the monovalent metal ion [or the proportion of the monovalent metal ion in the shell (if the soft capsule contains a content, the proportion of the monovalent metal ion in the shell)] is not particularly limited, and may be selected from a range of about 0.01% by mass or more (e.g., 0.03% by mass or more) in terms of solid content [or the proportion to the total components other than the solvent such as water (components that make up the shell)], 0.05% by mass or more (e.g., 0.07% by mass or more), preferably 0.1% by mass or more, more preferably 0.3% by mass or more, particularly 0.5% by mass or more [e.g., 0.8% by mass or more (e.g., 1% by mass or more, 1.15% by mass or more)], etc., or 30% by mass or less, preferably 20% by mass or less (e.g., 18% by mass or less), more preferably 15% by mass or less (e.g., 12% by mass or less), particularly 10% by mass or less (e.g., 8% by mass or less, 5% by mass or less), etc.

[0024] When a monovalent metal ion is contained as a compound, the proportion of the monovalent metal compound [or the proportion of the monovalent metal compound in the coating (if the capsule contains a content, the proportion of the monovalent metal compound in the coating)] can be appropriately selected depending on the type of compound, the proportion (concentration) of the monovalent metal contained in the compound, and the like, and may be selected from a range of about 0.01% by mass or more (e.g., 0.03% by mass or more) in terms of solid content [or the proportion to the total components other than the solvent such as water (components constituting the coating)], and may be 0.1% by mass or more (e.g., 0.15 % or more), preferably 0.2% or more, more preferably 0.5% or more, and particularly 1% or more [for example, 1.5% or more (for example, 2% or more, 2.5% or more, 3% or more)], or it may be 80% or less by mass (for example, 70% or less by mass), preferably 60% or less by mass (for example, 55% or less by mass), more preferably 50% or less by mass (for example, 45% or less by mass), and particularly 40% or less by mass (for example, 35% or less, 30% or less, 25% or less, 20% or less by mass).

[0025] In particular, when a monovalent metal ion is contained as an organic compound (e.g., an alkali metal salt of a sugar or polysaccharide such as an alkali metal alginate), the proportion of the compound, calculated as solids [or as a proportion to all components other than the solvent such as water (components that make up the coating)], may be 0.1 mass% or more, preferably 1 mass% or more, more preferably 5 mass% or more, and particularly 10 mass% or more, and may be 80 mass% or less (e.g., 70 mass% or less), preferably 60 mass% or less (e.g., 55 mass% or less), more preferably 50 mass% or less (e.g., 45 mass% or less), and particularly 40 mass% or less.

[0026] Furthermore, when monovalent metal ions are contained, the proportion of monovalent metal ions may be, for example, 0.01 parts by mass or more (e.g., 0.05 parts by mass or more), preferably 0.1 parts by mass or more (e.g., 0.3 parts by mass or more), more preferably 0.5 parts by mass or more (e.g., 0.8 parts by mass or more), particularly 1 part by mass or more (e.g., 1.5 parts by mass or more, 2 parts by mass or more, 2.5 parts by mass or more, 3 parts by mass or more) relative to 100 parts by mass of gellan gum, or may be 100 parts by mass or less (e.g., 80 parts by mass or less), preferably 50 parts by mass or less (e.g., 40 parts by mass or less), more preferably 30 parts by mass or less (e.g., 25 parts by mass or less), or 20 parts by mass or less (e.g., 18 parts by mass or less, 15 parts by mass or less, etc.).

[0027] When a monovalent metal ion is contained as a compound, the ratio of the monovalent metal compound may be, for example, 0.1 parts by mass or more (e.g., 0.5 parts by mass or more), preferably 1 part by mass or more (e.g., 2 parts by mass or more), more preferably 3 parts by mass or more (e.g., 4 parts by mass or more), particularly 5 parts by mass or more (e.g., 7 parts by mass or more, 8 parts by mass or more, 10 parts by mass or more) relative to 100 parts by mass of gellan gum, or 500 parts by mass or less (e.g., 400 parts by mass or less), preferably 300 parts by mass or less (e.g., 250 parts by mass or less), more preferably 200 parts by mass or less (e.g., 150 parts by mass or less), or 120 parts by mass or less (e.g., 100 parts by mass or less, 90 parts by mass or less, 80 parts by mass or less, 70 parts by mass or less, etc.).

[0028] In particular, when a monovalent metal ion is contained as an organic compound (e.g., an alkali metal salt of a sugar or polysaccharide such as an alkali metal alginate), the proportion of the compound may be, for example, 0.1 parts by mass or more (e.g., 0.5 parts by mass or more), preferably 1 part by mass or more (e.g., 3 parts by mass or more), more preferably 5 parts by mass or more (e.g., 8 parts by mass or more), particularly 10 parts by mass or more (e.g., 15 parts by mass or more, 20 parts by mass or more, 25 parts by mass or more, 30 parts by mass or more) relative to 100 parts by mass of gellan gum, or may be 500 parts by mass or less (e.g., 400 parts by mass or less), preferably 350 parts by mass or less (e.g., 300 parts by mass or less), more preferably 250 parts by mass or less (e.g., 200 parts by mass or less), or may be 150 parts by mass or less (e.g., 120 parts by mass or less, 100 parts by mass or less), etc.

[0029] By using the monovalent metal ion (compound) in the above ratio, it is easy to efficiently obtain capsules that are favorable in terms of disintegration property, capsule strength, etc.

[0030] The capsule (or coating) of the present invention may or may not contain polyvalent metal ions (e.g., divalent metal ions such as calcium) in addition to the monovalent metal ions. If it does contain them, the content (content in the coating) is not particularly limited, but is preferably relatively small, and may be, for example, 5 parts by mass or less, preferably 3 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0.1 parts by mass or less of polyvalent metal ions (or polyvalent metals) per 100 parts by mass of monovalent metal ions (or monovalent metals). In addition, gellan gum may contain polyvalent metal ions (for example, as alkaline earth metal salts of the carboxyl groups that constitute gellan gum), but such polyvalent metals are not considered to fall under the above-mentioned "polyvalent metal ions" (polyvalent metals).

[0031] In the capsule (coating), gellan gum may be combined with other coating bases as necessary. Such other coating bases are not particularly limited, but include, for example, gelatin, carrageenan, agar, pectin, locust bean gum, xanthan gum, guar gum, tara gum, welan gum, tamarind seed gum, ghatti gum, psyllium seed gum, tragacanth gum, amaceous seed gum, diutan gum, gum arabic, curdlan, dasserellan, pullulan, glucomannan, alginic acid, their decomposition products (for example, guar gum decomposition products, etc.), their salts, etc. In particular, the capsule [the membrane (base) constituting the capsule] is preferably vegetable-based (mainly composed of vegetable ingredients). From this viewpoint, even when other membrane bases are used, the other membrane bases (or membranes) are preferably vegetable-based (mainly composed of vegetable ingredients), and typically, the capsule [the membrane (base) constituting the capsule)] is preferably free of (substantially free of) animal ingredients (e.g., gelatin, etc.).

[0032] Other coating bases may be used as components containing monovalent metal ions (monovalent metal compounds). For example, the above-mentioned alkali metal alginate may be used as other coating bases.

[0033] The other coating bases may be used alone or in combination of two or more.

[0034] When another coating base is used, the ratio of the other coating base is not particularly limited and may vary depending on the type of the other coating base, but the coating base may be composed such that gellan gum is the main component. For example, the ratio of the other coating base may be 200 parts by mass or less (e.g., 150 parts by mass or less), preferably 100 parts by mass or less, more preferably 80 parts by mass or less (e.g., 60 parts by mass or less, 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less) relative to 100 parts by mass of gellan gum. When another coating base is used, the lower limit is not particularly limited, but may be, for example, 0.1 parts by mass, 0.5 parts by mass, 1 part by mass, 2 parts by mass, 3 parts by mass, 5 parts by mass, 8 parts by mass, 10 parts by mass, 12 parts by mass, 15 parts by mass, etc. relative to 100 parts by mass of gellan gum. As described above, the other coating base is preferably vegetable-based. Therefore, even if the other coating base contains an animal component (gelatin, etc.), the proportion of the animal component (gelatin, etc.) may be about 10 parts by mass or less relative to 100 parts by mass of gellan gum, or may be substantially free of the animal component (gelatin, etc.) [for example, 5 parts by mass or less (for example, 3 parts by mass or less, 2 parts by mass or less, 1 part by mass or less, 0 parts by mass) relative to 100 parts by mass of gellan gum].

[0035] The capsule (shell) may further contain a plasticizer, for example, from the viewpoint of adjusting the strength of the shell. Any plasticizer known in the art may be used without any particular limitation. Specifically, for example, polyhydric alcohols (e.g., (poly)alkylene glycols such as ethylene glycol, propylene glycol, polyethylene glycol, and polypropylene glycol; polyols having three or more hydroxyl groups such as glycerin), sugars [e.g., monosaccharides (e.g., glucose, fructose, glucose, galactose, etc.), disaccharides (e.g., sucrose, maltose, trehalose, coupling sugar, etc.), oligosaccharides (e.g., maltooligosaccharides, etc.), sugar alcohols (e.g., sorbitol, maltitol, lactose, etc.), and the like may be used. Examples of suitable saccharides include cellulose, cellulose acetate, cellulose syrup, etc., cellulose derivatives (e.g., cellulose acetate, cellulose syrup, etc.), polysaccharides or derivatives thereof (e.g., starch, starch derivatives (e.g., polydextrose, dextrin, maltodextrin, resistant dextrin, cyclodextrin (α, β or γ)), cellulose derivatives (e.g., hydroxypropyl cellulose, hydroxypropylmethyl cellulose, methyl cellulose, carboxymethyl cellulose), etc.), polyvinyl alcohol, triacetin, etc.

[0036] These may be used alone or in combination of two or more.

[0037] Among them, polyhydric alcohols, sugar alcohols, disaccharides, polysaccharides, and derivatives thereof (e.g., polysaccharide derivatives such as starch derivatives and cellulose derivatives) are preferred from the viewpoints of imparting elasticity to the capsule after drying, improving water disintegration, improving the feel or texture of the shell, improving the operability (ease of handling) of the shell liquid, and shortening the drying time of the capsule by adding a plasticizer to increase the solid concentration in the shell liquid, and among them, glycerin, propylene glycol, sorbitol, erythritol, trehalose, starch, starch derivatives, and cellulose derivatives are more preferred. For example, when the plasticizer is contained in the shell, the content of the plasticizer in the shell is not particularly limited, and may be, for example, 10 to 50% by mass.

[0038] The capsule (shell) may contain, in addition to the above-mentioned components, components known in the art. Examples of such components include colorants (dyes, pigments), flavorings, sweeteners, antioxidants, preservatives, seasonings, spices, acidulants (e.g., citric acid or its salts), bittering agents, salt, umami components, and other components described in the section on contents below (e.g., physiologically active substances, biologically active substances, etc.). These may be used alone or in combination of two or more. Depending on the type, the sweetener may also be used as a shell base or plasticizer as described above. The content of the above-mentioned components is not particularly limited and may be, for example, 50% by mass or less.

[0039] As described above, the capsule may be composed of only a membrane, or may be composed of a membrane and a content. In the capsule having such a content, the capsule content is not particularly limited. The shape of the content is not particularly limited, and may be, for example, liquid, solid, or a mixture of these.

[0040] Specific ingredients include, for example, fragrances, cosmetics, surfactants, detergents, bath additives, cooling agents, physiologically active substances (for example, vitamins, amino acids, collagen, collagen peptides, lipids {oils and fats [oils (for example, medium chain fatty acid oil (MCT), olive oil, fish oil, flaxseed oil, etc.), fats (for example, butter, margarine, coconut oil, shea butter, etc.)], waxes, etc.}, isoflavones, minerals, enzymes, hormones, etc.), biologically active substances (medicines, etc.), microorganisms (for example, bacteria such as lactic acid bacteria, bifidobacteria, natto bacteria, yeast fungi, etc.; fungi such as yeast, etc.), foods and beverages (or extracts thereof), plants (or extracts thereof), sweeteners, acidulants, seasonings, tonics, etc. These may be used alone or in combination of two or more.

[0041] The content of the content in the capsule is not particularly limited and can be appropriately set depending on the size of the capsule and its purpose. For example, the mass ratio of the content to the shell may be 1:1 or more for the content.

[0042] The capsule (soft capsule) may be a seamless capsule. Representative capsules (soft capsules) include seamless capsules having a content and a shell.

[0043] The shape of the capsule is not particularly limited, but may be, for example, spherical (such as a perfect sphere) or football-shaped.

[0044] The outer diameter of the capsule is not particularly limited, and may be 0.1 mm or more, 0.5 mm or more, 1 mm or more, 1.5 mm or more, 2 mm or more, etc., or 30 mm or less, 25 mm or less, 20 mm or less, 18 mm or less, 15 mm or less, 12 mm or less, 10 mm or less, 8 mm or less, etc., and may typically be 0.1 to 20 mm (e.g., 0.1 to 15 mm), 1 to 15 mm, 1.5 to 10 mm, 2 to 8 mm, etc. The outer diameter means the major axis when the planar shape (cross section) of the capsule is circular, and means the maximum diameter when it is not circular. The outer diameter can be measured, for example, using a digital caliper (product name: Quick Mini 25, model number: PK-0510SU, measurement range: 0 to 25 mm, manufactured by Mitutoyo). When the capsule does not have a content (or consists only of a shell), the outer diameter is the diameter of the shell. The outer diameter may be a measurement value under a given condition (e.g., 40-60% RH, 45% RH, etc.). Hereinafter, unless otherwise specified, such as "before drying," the same applies to the physical properties of the soft capsule (e.g., shell thickness, breaking strength, elasticity, etc.).

[0045] When the capsule has a content, the thickness of the capsule shell is not particularly limited and may be, for example, about 5 to 120 μm, 10 to 100 μm, 20 to 90 μm, or 20 to 60 μm. The thickness of the coating can be measured, for example, using a digital microscope (product name: VHX-900, manufactured by Keyence).

[0046] When the capsule has contents, the mass ratio of the shell to the contents can be selected depending on the thickness (outer diameter) of the capsule, and is not particularly limited, but can be selected from a range of about 1 part by mass or more (e.g., 10 parts by mass or more) of contents per 100 parts by mass of the shell, preferably 30 parts by mass or more (e.g., 50 parts by mass or more), more preferably 60 parts by mass or more (e.g., 100 parts by mass or more), and may be 4000 parts by mass or less (e.g., 3500 parts by mass or less), preferably 3000 parts by mass or less (e.g., 2500 parts by mass or less), more preferably 2000 parts by mass or less, etc.

[0047] Furthermore, the shell ratio of the capsule is not particularly limited, and may be, for example, 1 mass % or more, 2 mass % or more, 3 mass % or more, etc. When the capsule has a content, the upper limit of the shell ratio (mass ratio of the shell to the total amount of the shell and the content) is not particularly limited, and may be, for example, 80 mass %, 70 mass %, 60 mass %, 50 mass %, 40 mass %, 35 mass %, 30 mass %, 25 mass %, 22 mass %, 20 mass %, 18 mass %, etc. In particular, when the capsule has a content, the coating ratio may be, for example, 1 to 50 mass% (e.g., 2 to 40 mass%), preferably 3 to 20 mass%, more preferably about 3 to 18 mass%, and usually 3 to 50 mass% (e.g., about 3 to 40 mass%). In addition, when a capsule has no content (or consists only of a shell), the shell ratio is 100% by mass. Of course, the present invention also includes such capsules having no content (capsules with a shell ratio of 100%).

[0048] The moisture content of the capsule (moisture content in the shell) can be appropriately set depending on the application of the capsule, and may be, for example, 30% by mass or less, 25% by mass or less, 20% by mass or less, 1% by mass or more, 3% by mass or more, 5% by mass or more, 8% by mass or more, etc. For practical purposes, the moisture content may be 10 to 18% by mass, etc. The moisture content is not particularly limited and can be determined using a conventional method [for example, a method of measuring loss on drying (a method using the mass before and after drying)].

[0049] The capsule of the present invention can often achieve sufficient water disintegration (excellent water disintegration). In such a case, the capsule may have a relatively short disintegration time (for example, within 60 minutes) according to the Japanese Pharmacopoeia (17th revision) disintegration test method using water (37±2°C) as the test liquid, and the disintegration time may be within 40 minutes, within 30 minutes, etc., and particularly within 20 minutes, within 10 minutes, etc. The lower limit of the disintegration time is not particularly limited, and may be, for example, 30 seconds, 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, etc. In the disintegration test, an auxiliary disk may be used as necessary.

[0050] The breaking strength of the capsule depends on the outer diameter, etc., but may be, for example, 100 g or more, 200 g or more, 300 g or more, 400 g or more, 500 g or more, 600 g or more, 700 g or more, 800 g or more, 900 g or more, 1000 g or more. The upper limit of the capsule's breaking strength is not particularly limited, and may be, for example, 20,000 g or less, 15,000 g or less, 12,000 g or less, 10,000 g or less, or the like. The breaking strength can be measured, for example, by a rheometer CR-3000EX (manufactured by Sun Scientific Co., Ltd.).

[0051] In a capsule (e.g., a capsule having a content), the ratio of breaking strength (g) to outer diameter (mm) (breaking strength / outer diameter) is not particularly limited, but may be, for example, 200 or more (e.g., more than 200), preferably 210 or more (e.g., 220 or more), more preferably 230 or more (e.g., 240 or more), or may be 250 or more, 300 or more, 400 or more, etc. The upper limit of the ratio of breaking strength to outer diameter (breaking strength / outer diameter) is not particularly limited, and may be, for example, 20,000, 15,000, 10,000, 8,000, 6,000, 5,000, or the like.

[0052] Since it is conceivable that a capsule may be easily broken even if it has a high breaking strength (for example, when the outer diameter is large), the ratio of breaking strength to outer diameter can be said to be an index that reflects the actual ease of breaking a capsule.

[0053] The rupture distance of the capsule depends on the outer diameter, etc., but may be, for example, 0.1 mm or more, 0.2 mm or more, 0.5 mm or more, 1.0 mm or more, etc. The upper limit of the breaking distance of the soft capsule is not particularly limited, but may be, for example, 15 mm or less, 10 mm or less, 8 mm or less, etc. The breaking distance can be measured, for example, by a rheometer CR-3000EX (manufactured by Sun Scientific Co., Ltd.).

[0054] In the capsule, the ratio of the breaking distance (mm) to the outer diameter (mm) (breaking distance / outer diameter) is not particularly limited, but may be, for example, 0.1 or more, preferably 0.12 or more, more preferably 0.15 or more, or may be 0.18 or more, 0.2 or more, etc.

[0055] The upper limit of the ratio of the breaking distance to the outer diameter (breaking distance / outer diameter) is not particularly limited, and may be, for example, 1.0, 0.98, 0.97, 0.96, 0.95, or the like.

[0056] The ratio of the breaking distance to the outer diameter can be said to represent the degree of elasticity (how easily the capsule can deform before breaking), and thus can be said to be an indicator that supplementarily reflects the strength (ease of breaking) of the capsule.

[0057] The capsule of the present invention often has such a relatively high (or sufficient) mechanical strength. In a particularly preferred embodiment of the capsule of the present invention, the capsule may have both such mechanical strength and the above-mentioned water disintegrability while containing gellan gum. Generally, it is necessary to increase the capsule shell thickness (shell ratio) so that the capsule can withstand the manufacturing process (especially the drying process), but increasing the shell thickness tends to deteriorate the water disintegration property. In other words, it is difficult to achieve sufficient mechanical strength and disintegration property at the same time in a capsule. In particular, according to the study by the present inventor, this tendency was particularly noticeable in capsules containing gellan gum in the shell. However, in the present invention, by adjusting the coating formulation, it is possible to efficiently achieve both of these. Furthermore, such capsules can be produced efficiently by appropriately selecting the components to be combined with gellan gum (e.g., monovalent metal ions or metal compounds, other coating bases, plasticizers, and other components) and their ratios (as well as the capsule production conditions).

[0058] In the present invention, multiple capsules can be obtained in a relatively uniform form. For example, in a capsule (multiple capsules), the standard deviation (SD) value of the breaking strength may be, for example, 800 g or less, 700 g or less, 600 g or less, 500 g or less, 400 g or less, 350 g or less, depending on the breaking strength, etc. In addition, for a capsule (multiple capsules), the standard deviation (SD) value of the breaking distance may be, for example, 2 mm or less, 1.5 mm or less, 1 mm or less, 0.8 mm or less, 0.7 mmg or less, 0.6 mm or less, 0.5 mm or less, etc., depending on the breaking strength, etc.

[0059] Capsules (soft capsules) can be produced according to known methods. For example, they may be produced by a dropping method [a dropping method using a nozzle (e.g., a multiple nozzle)] using a liquid (coating liquid) containing components corresponding to the capsule (or coating) (e.g., gellan gum, and other components such as monovalent metal compounds, other coating bases, and plasticizers).

[0060] Generally, the coating solution often contains water as a solvent component.

[0061] In the coating solution, the solids concentration may be, for example, 3 mass% or more (e.g., 4 mass% or more), preferably 5 mass% or more, and more preferably 6 mass% or more, and may be 20 mass% or less (e.g., 15 mass% or less), preferably 12 mass% or less, and more preferably 10 mass% or less.

[0062] The production conditions can be appropriately set depending on the capsule composition, capsule diameter, shell ratio, etc. In addition, the cooling temperature, cooling time, drying temperature, and drying time after dropping can also be appropriately set.

[0063] After the dropping, the capsules may be immersed in an immersion liquid (e.g., a liquid containing polyvalent metal ions such as calcium) before drying. However, in the present invention, since the capsules (coatings) are composed of the above-mentioned components, such immersion is not necessary, and may even impair water-disintegratability.

[0064] In the present invention, gelation can be efficiently promoted while providing gellan gum with an appropriate strength, and therefore, capsules (soft capsules) having an appropriate manufacturable strength and excellent physical properties (e.g., water disintegration property and mechanical strength) can be efficiently obtained in the present invention. As described above, the capsules of the present invention can be efficiently produced by the dropping method or the like. Typically, the capsules of the present invention can be produced by the dropping method through at least a capsule production step of obtaining capsules (capsules having a high water content) and a drying step of drying the capsules obtained through this capsule production step.

[0065] In this series of steps, by appropriately setting the conditions, particularly before drying (capsules before the drying step), it is possible to further reduce deformation and cracking after drying, thereby making it easier to achieve efficient production.

[0066] Before drying (capsule before drying), the moisture content (moisture content in the shell) is usually high, and may be, for example, 70% by mass or more, 75% by mass or more, 80% by mass or more, 85% by mass or more, 90% by mass or more, or 99% by mass or less, 98% by mass or less, 97% by mass or less, 96% by mass or less, 95% by mass or less, etc.

[0067] The outer diameter of the capsule before drying is not particularly limited, and is usually 0.1 mm or more (eg, 1 to 20 mm), and may be 0.75 to 22.5 mm, or 25 mm or less (eg, 0.5 to 25 mm). The outer diameter can be measured, for example, using a digital caliper (product name: Quick Mini 25, model number: PK-0510SU, measurement range: 0 to 25 mm, manufactured by Mitutoyo).

[0068] The breaking strength of the capsule before drying cannot be generally set depending on the outer diameter, but may be 10 g or more (e.g., 50 to 1000 g), 30 to 1500 g, 3000 g or less (e.g., 10 to 3000 g), etc. The breaking strength can be measured with a rheometer CR-3000EX (manufactured by Sun Scientific Co., Ltd.).

[0069] In the capsule before drying, the ratio of the breaking strength (g) to the outer diameter (mm) (breaking strength / outer diameter) may be 3 or more, 3.5 or more, 4 or more, 4.5 or more, and particularly 5.0 or more. If it is above the above value, the capsule obtained by drying has a strength that can be manufactured, but can be disintegrated in water. The breaking strength / outer diameter may be, for example, 5.5 or more, or 6.0 or more, from the viewpoint that the capsule does not break due to drying. The upper limit is not particularly limited, and may be, for example, 15 or less.

[0070] The capsule of the present invention can be manufactured by, for example, the manufacturing method as described above, but such a manufacturing method can also follow a specific known manufacturing method, for example, the method described in Japanese Patent No. 5047285 or Japanese Patent Publication No. 10-506841. Specific examples include a dropping method (seamless capsule method) using a double or multiple (triple or more) nozzle. For example, a manufacturing method including a step of preparing a filling by filling a capsule shell containing gellan gum (and other components such as monovalent metal ions) can be mentioned. After preparing the filling, a molding step and a drying step may be included. The capsule content may have the same composition as the capsule shell liquid, and may be set by referring to the above-mentioned section on the capsule of the present invention.

[0071] The dropping method uses, for example, a composite nozzle device that is appropriately aligned in a substantially concentric manner. The composite nozzle device has, for example, an inner nozzle that receives and distributes the capsule contents and an outer nozzle that receives and distributes the capsule shell liquid, and the inner nozzle and the outer nozzle are aligned in a substantially concentric manner. Using the composite nozzle device, the capsule contents are discharged from the outlet of the inner nozzle, and the capsule shell liquid is discharged from the outlet of the outer nozzle. The capsule contents and the capsule shell liquid are simultaneously discharged from the inner nozzle and the outer nozzle at a constant speed by a pump or gravity into an oil liquid or gas, respectively, forming a coaxial flow in a carrier flow flowing downstream, and a physical force such as vibration is applied to cut the discharged liquid at a constant interval, and the cut parts are made spherical due to the interface or surface tension between the oil liquid or gas and the capsule shell liquid, and the membrane layer is gelled by cooling, thereby producing a capsule.

[0072] The interfacial or surface tension is not particularly limited, but is preferably 15 to 50 mN / m at the interface between the capsule shell liquid and the content liquid, for example. For measuring the interfacial or surface tension, for example, Sigma702 manufactured by KSV INSTRUMENTS (FINLAND) is used.

[0073] In the present invention, it is preferable to appropriately control the temperature conditions near the multiple nozzle during capsule production. For example, it is preferable to set the temperature in the vicinity of the multiple nozzle of the capsule (seamless capsule) production device to the following range. (1) Controlling the temperature of the capsule contents to a set value ±2°C (more preferably ±1°C) within a range of a predetermined temperature at which the contents become liquid (or fluid) depending on the properties of the contents {for example, (i) if the contents are liquid (at room temperature), the temperature of the capsule contents is 5 to 25°C (more preferably 12 to 22°C); (ii) if the contents are solid at room temperature, the temperature at which the contents become liquid [for example, if fat (e.g., butter, margarine, or other oils that are at room temperature but below 40°C) is used, the temperature of the capsule contents is 30 to 60°C (more preferably 40 to 50°C), etc.], etc.}, (2) The temperature of the capsule shell liquid is controlled within the range of 50 to 99°C (more preferably 60 to 95°C) within ±2°C (more preferably ±1°C) of the set value. In addition, when a lipophilic solvent is added to the oily component of the capsule contents, (3) it is preferable to control the temperature of the lipophilic solvent within the range of 1 to 25°C (more preferably 5 to 20°C) within ±1°C (more preferably ±0.5°C) of the set value. In addition to the above conditions, (4) it is more preferable that the temperature difference between the capsule contents and the capsule shell liquid is 25° C. or more and 94° C. or less (more preferably 38° C. or more and 85° C. or less). In addition, when a lipophilic solvent is added to the oily component of the capsule contents, (5) it is more preferable that the difference in temperature between the capsule shell liquid and the lipophilic solvent is 35°C or more and 94°C or less (more preferably 49°C or more and 85°C or less). Furthermore, after passing through the nozzle, the membrane layer is cooled to gel by cooling, and then cooled by cooling oil. The cooling temperature by the cooling oil is, for example, about 5 to 35°C.

[0074] Those skilled in the art can select or combine the above temperature conditions (1) to (5) as appropriate according to the quality required for the capsule (seamless capsule). The above temperature control can be easily performed by those skilled in the art, for example, by combining PID control and feedback control, but is not limited to these control methods.

[0075] The capsule shell liquid is not particularly limited as long as it contains gellan gum (and other components such as monovalent metal ions, if necessary), and can be prepared, for example, by dissolving it in a solvent. The solvent is not particularly limited as long as it does not impede the effects of the present invention, and examples of the solvent include water and alcohols such as ethanol, with water being preferred.

[0076] Furthermore, when the obtained capsules are cooled, the cooling temperature is not particularly limited, but is usually not higher than 20° C., and preferably not higher than 10° C. The cooling time is not particularly limited, but is usually about 10 minutes to 30 hours.

[0077] After the wet capsules are produced by the above-mentioned method, they can be dried. This drying is generally performed using, for example, a "rotary drum type dryer" equipped with a ventilation device, and for small capsules such as seamless capsules, a fluidized type may be used in which the capsules are blown up and fluidized while being dried. The drying temperature is not particularly limited, but may be about 20 to 50°C. EXAMPLES

[0078] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these.

[0079] The obtained capsules were measured or evaluated according to the following methods. [Capsule breaking strength and elasticity (breaking distance)] The breaking strength of the capsules (capsules before and after drying) was measured at room temperature (22 to 27° C.) and 40 to 60% RH using a rheometer CR-3000EX manufactured by Sun Scientific Corporation. The strength of the dried capsules was measured after they had been left in an environment with a relative humidity of 45% for a sufficient period of time (about half a day) (the moisture content was generally about 10 to 18% by mass) (the same applies below for dried capsules). In the above measurements, the distance the capsule was deformed until it broke (the distance the capsule was pressed into the rheometer until it broke) was used as an index of the elasticity of the capsule. Furthermore, the standard deviation (SD) values ​​of the breaking strength and breaking distance were calculated (n=20). [Capsule outer diameter] The capsule outer diameter was measured at room temperature (22-27°C) and 40-60% RH using a digital caliper manufactured by Mitutoyo Corporation (product name: Quick Mini 25, model number: PK-0510SU, measurement range: 0-25 mm). [Capsule coating rate] The coating rate was calculated by the formula: coating rate (%)=capsule coating weight / total capsule weight×100. The weight was measured using an electronic balance GX-200 manufactured by A&D Co., Ltd. [Capsule shell thickness] The thickness of the capsule coating (coating thickness) was measured using a digital microscope manufactured by Keyence Corporation (product name: VHX-900, using a 10 μm calibration scale). [Capsule disintegration] The obtained capsules were tested according to the disintegration test method of the Japanese Pharmacopoeia (17th revision) by placing the capsule and an auxiliary disk in a tester and using water at 37±2°C as the test liquid, and the time when the capsule clearly lost its original shape or only fragments of the capsule membrane remained was defined as the disintegration time. Note that for the same formulation, at least 6 capsules were tested, and the average disintegration time of these capsules was defined as the disintegration time. [Moisture content] The moisture content was obtained by measuring the loss on drying as shown in the following formula. Loss on drying (%) = [capsule weight (mg) - dry capsule weight (mg)] / capsule weight (mg) x 100 The dry capsule weight was the capsule weight after the capsule was thoroughly dried (at 110° C. for 2 hours). [Cracks after drying] Capsules that had no cracks after drying were rated as "none" (0%), and those that had cracks were rated as the percentage of cracks.

[0080] Examples 1 to 8 A coating liquid was prepared according to the formula shown below (Table 1), and capsules (contents: MCT (Kao: Coconard ML)) were obtained using a dropping method with a multiple nozzle under the conditions shown in Table 4. The gellan gum used was deacylated (CP Kelco, "Kelcogel") (hereinafter the same). In addition, the proportion of monovalent metal (sodium) ions in sodium alginate was 0.0923 g per 1 g (same below).

[0081] [Table 1]

[0082] Comparative Example 1 A coating liquid was prepared according to the formula shown below (Table 2), and capsules (contents: MCT (Kao: Coconard ML)) were obtained using a dropping method with a multiple nozzle under the conditions shown in Table 4.

[0083] [Table 2]

[0084] Examples 9-10 A coating solution was prepared according to the formula shown below (Table 3), and capsules (contents: MCT (Kao: Coconard ML)) were obtained by a dropping method using a multiple nozzle under the conditions shown in Table 4. In Example 10, the capsules were immersed in an aqueous calcium lactate solution before drying. The proportion of monovalent metal (sodium) ions in sodium citrate is 0.0891 g per 1 g (the same applies below).

[0085] [Table 3]

[0086] The results are shown in Table 4.

[0087] [Table 4]

[0088] As is clear from the results in the above table, capsules excellent in water disintegrability and mechanical strength were obtained in the examples. In particular, the results of Example 9 show that by selecting the capsule manufacturing conditions (conditions before drying), capsules without cracks after drying can be efficiently obtained. Moreover, the results of Example 10 show that although the mechanical strength could be increased by the immersion treatment before drying, the capsules obtained had poor water-disintegrability. On the other hand, in Examples 1 to 8, capsules were obtained that were free of cracks and had both water disintegratability and excellent mechanical strength.

[0089] Examples 11 to 19 A coating liquid was prepared according to the formulation shown below (Table 5), and capsules (contents: MCT (Kao: Coconard ML)) were obtained using a dropping method with a multiple nozzle under the conditions shown in Table 6.

[0090] [Table 5]

[0091] In the coating liquid, the proportion of gellan gum relative to the total solid content was 18.75 mass% (Examples 11-12), 31.25 mass% (Examples 13-17), or 12.5 mass% (Examples 18-19), the proportion of sodium alginate was 12.5 mass% (0.092 mass% as monovalent metal), and the proportion of sodium alginate relative to 100 mass parts of gellan gum was 66.7 mass parts (6.15 mass parts as monovalent metal) [Examples 11-12], 40.0 mass parts (3.69 mass parts as monovalent metal) [Examples 13-17], or 100 mass parts (9.23 mass parts as monovalent metal) [Examples 18-19].

[0092] The results are shown in Table 6.

[0093] [Table 6]

[0094] From the above, it was found that capsules with sufficient water disintegrability and mechanical strength can be obtained even if other coating bases (agar, carrageenan, pectin) are mixed with gellan gum. In particular, the results of Examples 11 to 17 and Examples 18 and 19 demonstrated that by appropriately selecting the proportion of gellan gum in the overall coating base (ensuring that the proportion is not too small), it is possible to efficiently achieve both water disintegrability and mechanical strength. Furthermore, from the results of Example 18, it was found that even when other coating bases are used, by selecting the capsule manufacturing conditions (conditions before drying), capsules that are free of cracks after drying tend to be obtained efficiently.

[0095] Examples 20 to 26 A coating solution was prepared according to the formula shown below (Table 7), and capsules (contents: MCT (Kao: Coconard ML)) were obtained by a dropping method using a multiple nozzle under the conditions shown in Table 8. Example 7 is also shown for comparison. In addition, the proportion of monovalent metal (potassium) ions in the K alginate was 0.112 g per 1 g.

[0096] [Table 7]

[0097] In the coating solution, the proportion of gellan gum relative to the total solid content was 37.5 mass%, and the proportion of the monovalent metal compound was 3.75 mass% (1.48 mass% as monovalent metal) [Example 20], 3.75 mass% (1.97 mass% as monovalent metal) [Example 21], 15.0 mass% (2.14 mass% as monovalent metal) [Example 22], 15.0 mass% (2.47 mass% as monovalent metal) [Example 23], 37.5 mass% (3.46 mass% as monovalent metal) [Example 24], 37.5 mass% (3.95 mass% as monovalent metal) [Example 25], 37.5 mass% (4.20 mass% as monovalent metal) % by mass [Example 26], and the ratio of the monovalent metal compound to 100 parts by mass of gellan gum is 10.0 parts by mass (3.93 parts by mass as monovalent metal) [Example 20], 10.0 parts by mass (5.25 parts by mass as monovalent metal) [Example 21], 40.0 parts by mass (5.70 parts by mass as monovalent metal) [Example 22], 40.0 parts by mass (6.57 parts by mass as monovalent metal) [Example 23], 100 parts by mass (9.23 parts by mass as monovalent metal) [Example 24], 100 parts by mass (10.54 parts by mass as monovalent metal) [Example 25], and 100 parts by mass (11.20 parts by mass as monovalent metal) [Example 26].

[0098] The results are shown in Table 8.

[0099] [Table 8]

[0100] As is clear from the results in the above table, capsules excellent in water disintegrability and mechanical strength were obtained even when various monovalent alkali metal salts were used.

[0101] Examples 27 to 31 A coating solution was prepared according to the formula shown in Table 9 below, and capsules (contents: MCT (Kao: Coconard ML)) were obtained by a dropping method using a multiple nozzle under the conditions shown in Table 10. Example 24 is also shown for comparison.

[0102] [Table 9]

[0103] In the coating solution, the proportion of gellan gum relative to the total solid content was 30.0% by mass, the proportion of sodium alginate was 30.0% by mass (2.77% by mass as monovalent metal), and the proportion of sodium alginate per 100 parts by mass of gellan gum was 100 parts by mass (9.23 parts by mass as monovalent metal).

[0104] The results are shown in Table 10.

[0105] [Table 10]

[0106] As is clear from the results in the above table, capsules excellent in water disintegrability and mechanical strength were obtained even when various plasticizers were used.

[0107] Examples 32 to 33 A coating solution was prepared according to the formulation shown below (Table 11), and capsules (single spheres) consisting of only the coating and no content were obtained using a dropping method using a single nozzle.

[0108] [Table 11]

[0109] In the coating liquid, the proportion of gellan gum relative to the total solid content was 20.0 mass%, the proportion of sodium alginate was 26.7 mass%, and the proportion of sodium alginate per 100 mass parts of gellan gum was 133 mass parts (12.31 mass parts as monovalent metal).

[0110] The results are shown in Table 12.

[0111] [Table 12]

[0112] As is clear from the results in the above table, capsules having excellent water-disintegrability and mechanical strength were obtained even when they contained no contents.

[0113] Examples 34 to 35 A coating liquid was prepared with the same recipe as in Example 24 (Table 9), and capsules were obtained by a dropping method using a multiple nozzle under the conditions shown in Table 13 [Contents of Example 34: refined olive oil (Dcoop S. Coop. And.: olive oil refined), Contents of Example 35: fish oil (Maruha Nichiro: DHA-46MK) 80% by mass and MCT (Kao: Coconard ML) 20% by mass]. For comparison, Example 24 is also shown.

[0114] The results are shown in Table 13.

[0115] [Table 13]

[0116] As is clear from the results in the above table, capsules excellent in water disintegrability and mechanical strength were obtained even when the contents were changed.

[0117] Examples 36 to 43 A shell liquid was prepared according to the formula in Table 14 below (formulation in Table 1 (Examples 1 to 8) except that no sodium alginate was used, and the total amounts of sodium alginate and hydrolyzed guar gum were all hydrolyzed guar gum), and capsules [contents: MCT (Kao: Coconard ML)] were obtained under the conditions shown in Table 15 by a dropping method using a multiple nozzle. For comparison, Examples 1 to 8 are also shown.

[0118] [Table 14]

[0119] The results are shown in Table 15.

[0120] [Table 15] [Industrial Applicability]

[0121] The capsule of the present invention can be suitably used in the fields of medicine, food, industry, etc.

Claims

1. A soft capsule having a shell that is substantially free of gelatin and contains gellan gum, The proportion of gellan gum in the coating is 10% by mass or more in terms of solid content, The coating contains a monovalent metal ion as a monovalent metal compound, The ratio of the monovalent metal compound is 150 parts by mass or less per 100 parts by mass of gellan gum, the coating does not contain polyvalent metal ions or contains polyvalent metal ions in a content ratio of 5 parts by mass or less of polyvalent metal ions per 100 parts by mass of monovalent metal ions, A soft capsule that satisfies the following (A) and / or (B): (A) The disintegration time according to the Japanese Pharmacopoeia Disintegration Test Method using water as the test liquid is within 60 minutes. (B) The ratio of breaking strength (g) to outer diameter (mm) (breaking strength / outer diameter) is 210 or more.

2. A soft capsule having a shell containing substantially no gelatin, gellan gum, and a monovalent metal ion, The proportion of gellan gum in the coating is 10% by mass or more in terms of solid content, The coating contains a monovalent metal ion as a monovalent metal compound, The ratio of the monovalent metal compound is 150 parts by mass or less per 100 parts by mass of gellan gum, the coating does not contain polyvalent metal ions or contains polyvalent metal ions in a content ratio of 5 parts by mass or less of polyvalent metal ions per 100 parts by mass of monovalent metal ions, A soft capsule that satisfies the following (A) and (B). (A) The disintegration time according to the Japanese Pharmacopoeia Disintegration Test Method using water as the test liquid is within 60 minutes. (B) The ratio of breaking strength (g) to outer diameter (mm) (breaking strength / outer diameter) is 210 or more.

3. A soft capsule having a coating containing gellan gum and a monovalent metal ion, The proportion of gellan gum in the coating is 10% by mass or more in terms of solid content, The coating contains a monovalent metal ion as a monovalent metal compound, The monovalent metal compound contains an alkali metal alginate, The ratio of the monovalent metal compound is 150 parts by mass or less per 100 parts by mass of gellan gum, A soft capsule that satisfies the following (A) and / or (B): (A) The disintegration time according to the Japanese Pharmacopoeia Disintegration Test Method using water as the test liquid is within 60 minutes. (B) The ratio of breaking strength (g) to outer diameter (mm) (breaking strength / outer diameter) is 210 or more.

4. A soft capsule having a coating containing gellan gum and a monovalent metal ion, The coating contains another coating base in an amount of 100 parts by mass or less per 100 parts by mass of gellan gum, the coating does not contain polyvalent metal ions or contains polyvalent metal ions in a content ratio of 5 parts by mass or less of polyvalent metal ions per 100 parts by mass of monovalent metal ions, A soft capsule that satisfies the following (A) and / or (B): (A) The disintegration time according to the Japanese Pharmacopoeia Disintegration Test Method using water as the test liquid is within 60 minutes. (B) The ratio of breaking strength (g) to outer diameter (mm) (breaking strength / outer diameter) is 210 or more.

5. 5. The capsule according to claim 1, 3 or 4, which has (A) a disintegration time of 60 minutes or less according to the Japanese Pharmacopoeia Disintegration Test Method using water as the test liquid, and (B) a ratio of breaking strength (g) to outer diameter (mm) (breaking strength / outer diameter) of 210 or more.

6. (C) A capsule according to any one of claims 1 to 5, wherein the ratio of the breaking distance (mm) to the outer diameter (mm) (breaking distance / outer diameter) is 0.1 or more.

7. The capsule according to any one of claims 4 to 6, wherein the proportion of gellan gum in the shell is 5% by mass or more.

8. The capsule according to any one of claims 4 to 7, which contains a monovalent metal ion as a monovalent metal compound.

9. The capsule according to any one of claims 1, 2, and 4 to 8, which contains a monovalent metal ion as at least one monovalent metal compound selected from the group consisting of an alkali metal halide, an alkali metal salt of an organic acid, and an alkali metal salt of a sugar or polysaccharide.

10. The capsule according to any one of claims 1, 2, and 4 to 9, which contains a monovalent metal ion at least as an alkali metal alginate.

11. The capsule according to any one of claims 1 to 10, wherein the proportion of monovalent metal ions is 0.1 parts by mass or more per 100 parts by mass of gellan gum, calculated as metal atoms.

12. The capsule according to any one of claims 1 to 3 and 5 to 11, wherein the shell contains another shell base in an amount of 100 parts by mass or less per 100 parts by mass of gellan gum.

13. The capsule according to any one of claims 1 to 12, wherein the shell contains a plasticizer.

14. The capsule according to any one of claims 1 to 13, wherein the shell contains at least one plasticizer selected from the group consisting of polyhydric alcohols, sugar alcohols, disaccharides, polysaccharides, and derivatives thereof.

15. The capsule according to any one of claims 1 to 14, wherein the outer diameter of the capsule is 0.1 to 15 mm.

16. The capsule according to any one of claims 1 to 15, wherein the capsule has a shell rate of 3% by mass or more.

17. The capsule according to any one of claims 1 to 16, which has a content and has a shell ratio of 3 to 50 mass %.

18. 18. The capsule according to any one of claims 1 to 17, wherein the standard deviation (SD) value of the breaking strength is 500 g or less and the standard deviation (SD) value of the breaking distance is 1 mm or less.

19. The capsule according to any one of claims 1 to 18, which is a seamless capsule.

20. A method for producing the capsule according to any one of claims 1 to 19, comprising at least a capsule production step of obtaining capsules having a moisture content of 80% by mass or more and a ratio of breaking strength (g) to outer diameter (mm) (breaking strength / outer diameter) of 5.0 or more by a dropping method, and a drying step of drying the capsules obtained by the capsule production step.

Citation Information

Patent Citations

  • Dropping pill with sodium alginate and gellan gum as capsule wall material, and its production technology

    CN104338145A

  • Sodium alginate / starch-based enteric hollow capsule and one-shot molding preparation method thereof

    CN104887643A

  • Automatic filler for highly sticky article

    JP1980029415A

  • Soft capsule

    JP2009028544A

  • Soft capsule film composition

    JP2009040716A